2020
DOI: 10.1177/0891988720915517
|View full text |Cite
|
Sign up to set email alerts
|

Age of Diagnosis and Comorbid PLMD Predict Poor Response of REM Behavior Disorder to Clonazepam

Abstract: Previous studies have shown the therapeutic effects of clonazepam for rapid eye movement sleep behavior disorder (RBD), but they had several limitations such as the lack of clear definition of treatment outcomes and little information about adjuvant therapy. The aims of this study were to evaluate the treatment outcomes with clonazepam and to explore possible determinants of treatment response. We performed a retrospective medical chart review of 171 patients with RBD. All the participants underwent overnight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Table 1 summarizes the studies describing the effect of clonazepam in patients with RBD [1,2,[17][18][19][20][21][22][23][24][25][26][27][28]. Surprisingly, despite clonazepam being considered a first-line therapy for RBD (and according to the experience of the authors of this review, it is a useful drug for treating this condition), its efficacy in the treatment of iRBD has apparently not been proven in randomized trials.…”
Section: Clonazepammentioning
confidence: 99%
“…Table 1 summarizes the studies describing the effect of clonazepam in patients with RBD [1,2,[17][18][19][20][21][22][23][24][25][26][27][28]. Surprisingly, despite clonazepam being considered a first-line therapy for RBD (and according to the experience of the authors of this review, it is a useful drug for treating this condition), its efficacy in the treatment of iRBD has apparently not been proven in randomized trials.…”
Section: Clonazepammentioning
confidence: 99%
“…reported that iRBD patients who phenoconverted to a parkinsonian disorder had significantly much higher PLMS index at baseline than iRBD patients who remained iRBD at follow‐up. In addition, the presence of PLMS has also been correlated with an increase in the percentage of RSWA in REM sleep, suggesting a greater severity of the disorder in these patients 54 and that PLMS during sleep increase with age 55,56 and are associated with striatal neurodegeneration and dopamine deficiency 57 …”
Section: Discussionmentioning
confidence: 99%
“…However, in these patients the best response for reducing PLMS was observed, compared to the other groups; this is very interesting considering that, in 1996, Schenck et al 53 reported that iRBD patients who phenoconverted to a parkinsonian disorder had significantly much higher PLMS index at baseline than iRBD patients who remained iRBD at follow-up. In addition, the presence of PLMS has also been correlated with an increase in the percentage of RSWA in REM sleep, suggesting a greater severity of the disorder in these patients 54 and that PLMS during sleep increase with age 55,56 and are associated with striatal neurodegeneration and dopamine deficiency. 57 The fact that the association of CLO and MLT acts positively on PLMS is a proof that they may be due to a complex mechanism not known, which however could involve supra and subtentorial networks.…”
Section: Clonazepammentioning
confidence: 97%
“…Several observational studies demonstrated its ability to suppress dream enactment behavior in isolated RBD and secondary RBD. 5,56 While its mechanism in improving RBD is unclear, it may work through enhanced GABA-ergic and glycinergic inhibition of spinal motor neurons. 57 Clonazepam may improve some phasic movements but does not appear to improve overall RWA, simple motor movements, or vocalizations, suggesting other mechanisms may be involved in major motor event suppression, such as through altering dream content.…”
Section: Key Pointsmentioning
confidence: 99%
“…Its use stemmed from its ability to control other types of movements during sleep and waking states. Several observational studies demonstrated its ability to suppress dream enactment behavior in isolated RBD and secondary RBD 5,56 . While its mechanism in improving RBD is unclear, it may work through enhanced GABA-ergic and glycinergic inhibition of spinal motor neurons 57 .…”
Section: Rapid Eye Movement Sleep Behavior Disordermentioning
confidence: 99%